Depressive symptoms during pregnancy and postpartum in women and use of antidepressant treatment – a longitudinal cohort study - Sunnqvist C; Sjöström K; Finnbogadóttir H (Dove Medical Press, 2019)
Charlotta Sunnqvist, Karin Sjöström, Hafrún Finnbogadóttir Faculty of Health and Society, Department of Care Science, Malmö University, Malmö, Sweden Objective: The aim of this study was to investigate whether women, who reported “symptoms of depression” during pregnancy and up to 1.5 years postpartum, who reported domestic violence or not, were treated with antidepressant medication. Patients and methods: A prospective longitudinal cohort study recruited primi- and multiparous women (n=1,939). The Edinburgh Postnatal Depression Scale (EPDS), the NorVold Abuse Questionnaire, and a questionnaire about medication during pregnancy were distributed and administered three times, during early pregnancy, late pregnancy, and the postpartum period. Antidepressant medication was compared between women with EPDS scores Results: EPDS scores ≥13 were detected in 10.1% of the women during the whole pregnancy, of those 6.2% had depressive symptoms already in early pregnancy and 10.0 % during the postpartum period. Women with EPDS scores ≥13 and non-exposure to domestic violence were more often non-medicated (P<0.001). None of the women with EPDS scores ≥13 exposed to domestic violence had received any antidepressant medication, albeit the relationship was statistically nonsignificant. Conclusion: Pregnant women who experienced themselves as having several depressive symptoms, social vulnerability, and even a history of domestic violence, did not receive any antidepressant treatment during pregnancy nor postpartum. This study shows the importance of detecting depressive symptoms during early pregnancy and a need for standardized screening methods. Keywords: antidepressant treatment, depression, domestic violence, postpartum, pregnancy, untreated, reproductive age